PENGEMBANGAN PELAYANAN PUBLIK BERBASIS E-GOVERNMENT DALAM PROGRAM LAYANAN PERIZINAN ONLINE (LAPERON) DI DPMPTSP KABUPATEN BADUNG - Wismayanti Wismayanti; Purnamaningsih Purnamaningsih (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2021)
Advances in communication and information technology bring many changes to the general habits of society. Communication and information technology is now inseparable from people's lives in this era. With digitalization, people can disseminate and obtain information widely without requiring a long time. The benefits of this easy, cheap, and fast technology have in common with the concept of excellent public service which is the hope of the community. In public services, people want services that are easily accessible, do not incur a lot of costs, and also do not require a long time to receive public services. To provide excellent service in this era of rapid technological progress and the government can optimize the use of information and communication technology in governance, which is known as E-government. Through the development of public service innovations based on E-government, it is expected to be able to provide services that are in accordance with the principles of good governance, so as to improve service quality and community satisfaction. Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) of Badung Regency builds public service innovations called Layanan Perizinan Online (LAPERON). This study uses qualitative research methods through secondary data collection. The development of public services in the LAPERON application can be seen from the availability of LAPERON on the website and also the Mobile Application with various features that make it easier for the public to apply for licensing services.